Significance of the Leading Programming Languages (International Journal of Innovative Research in Computer Science & Technology, 2021)
In today's technology era, programming is  more essential than ever. Python and C++ are the most  widely used programming languages. Python, the most  popular programming language of the twenty-first century,  is a higher-level object-oriented language, while C++ (the  language that powers most operating systems) is a lower level object-oriented language. Python and C++ are  compared in this article. This book covers an introduction  to various languages, memory management techniques, and  reasons for their program execution speed. Furthermore,  this study looked at the execution time and memory  requirements of a variety of algorithms in both languages,  comparing the best, average, and worst situations in each  language. Furthermore, they are compared in terms of their  benefits and drawbacks. C++ is faster than Python in terms  of execution speed, according to the findings, but Python is  a better option for beginners due to its simplicity. Aside  from that, the language should be selected depending on the  project type in order to get the best results. Programmers  play a crucial role in computing. C/C++, Python, and Java  are the most common languages. Beginning programming  classes often utilize C++ and Java. Python has grown in  popularity as an introductory programming language due to  a variety of reasons. As an entry-level programming  language, C, C++, Java, and Python were compared. More  students selected Python over C++ because of its simpler  pseudo-code syntax, better learning environment, and  greater abstraction.
Keywords: C; C++; Java; Memory; Programming Languages; Python